2012
DOI: 10.1007/s00426-012-0456-6
|View full text |Cite
|
Sign up to set email alerts
|

The processing of Arabic numbers is under cognitive control

Abstract: In this study, we evaluated whether the processing of two-digit Arabic numbers is subject to cognitive control. Participants performed a number comparison task with unit-decade compatible trials (36-47) and unit-decade incompatible number pairs (37-46). The unit-decade compatibility (incompatible minus compatible trials) was considered an index of conflict situation in numerical processing. To examine whether participants adapted to numerical conflict, we manipulated the percentage of incompatible trials relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
51
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 18 publications
6
51
0
Order By: Relevance
“…Hence, the computational model predicts that also the comparison of decimal fractions should be under cognitive control modulating the relevance of tenth and hundredth digits. Regarding the tenth–hundredth compatibility effect, we would expect it to be more pronounced in a stimulus set with a smaller proportion of incompatible relative to compatible number pairs, as found by Macizo and Herrera (2013) for the case of two-digit numbers. Moreover, in the original computational model (Huber et al, 2013c) cognitive control was implemented to act locally on a trial-by-trial basis and, thereby, it was able to simulate the Gratton effect in two-digit number comparison.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Hence, the computational model predicts that also the comparison of decimal fractions should be under cognitive control modulating the relevance of tenth and hundredth digits. Regarding the tenth–hundredth compatibility effect, we would expect it to be more pronounced in a stimulus set with a smaller proportion of incompatible relative to compatible number pairs, as found by Macizo and Herrera (2013) for the case of two-digit numbers. Moreover, in the original computational model (Huber et al, 2013c) cognitive control was implemented to act locally on a trial-by-trial basis and, thereby, it was able to simulate the Gratton effect in two-digit number comparison.…”
Section: Discussionmentioning
confidence: 81%
“…It was able to account for the proportion congruity effect found by Macizo and Herrera (2013) and predicted a Gratton effect (Gratton et al, 1992) in two-digit number comparison. Hence, the computational model predicts that also the comparison of decimal fractions should be under cognitive control modulating the relevance of tenth and hundredth digits.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, it has been observed that contextual effects during the processing of two-digit numbers not only increase the compatibility effect (Macizo & Herrera, 2011a) but this effect can be reduced too. Macizo and Herrera (2013) focused on the compatibility effect with two-digit Arabic digits. To evaluate the adaptation to conflict, the authors manipulated the percentage of incompatible trials relative to the percentage of compatible trials (20, 50, 80 % incompatible trials).…”
mentioning
confidence: 99%
“…For instance, when the proportion of incongruent trials in the Stroop task decreases, interference caused by them increases (MacLeod, 1991). Analogously in the multi-digit number comparison task, as the ratio of incompatible vs. compatible trials decreases, the unit-decade compatibility effect gets stronger (Macizo and Herrera, 2013; Huber et al, 2016). …”
Section: Attention and Conflict Monitoringmentioning
confidence: 99%